Clinical and radiographic analysis of an optimized rhBMP-2 formulation as an autograft replacement in posterolateral lumbar spine arthrodesis - Dimar, 2nd, John R; Glassman, Steven D; Burkus, J Kenneth; Pryor, Philip W; Hardacker, James W; Carreon, Leah Y (Journal of bone and joint surgery. American volume, 2009)
Previous studies have demonstrated the ability of recombinant human bone morphogenetic protein to achieve a solid fusion in anterior lumbar interbody arthrodesis. The purpose of this study was to compare iliac crest bone graft and recombinant human bone morphogenetic protein-2, combined with a carrier consisting of bovine collagen and beta-tricalcium phosphate-hydroxyapatite to create a compression-resistant matrix, for instrumented single-level posterolateral arthrodesis. Four hundred and sixty-three patients with symptomatic single-level lumbosacral degenerative disease with no greater than grade-1 spondylolisthesis were treated with single-level instrumented posterolateral arthrodesis through an open midline approach. Patients were randomly assigned to either the recombinant human bone morphogenetic protein-2 matrix group (239 patients) or the autogenous iliac crest bone-graft group (224 patients). The Oswestry Disability Index, Short Form-36, and back and leg pain scores were determined preoperatively and at 1.5, three, six, twelve, and twenty-four months postoperatively. Radiographs and computed tomography scans were made at six, twelve, and twenty-four months postoperatively to evaluate for fusion. The mean operative time and mean blood loss in the recombinant human bone morphogenetic protein-2 matrix group (2.5 hours and 343.1 mL, respectively) were significantly less than those in the iliac crest bone-graft group (2.9 hours and 448.6 mL). Both groups showed similar improvements in clinical outcomes and reduced pain. At twenty-four months, 60% of the iliac crest bone-graft group reported donor-site pain. At twenty-four months, fusion was evident in 96% of the patients in the recombinant human bone morphogenetic protein-2 matrix group compared with 89% in the iliac crest bone-graft group (p = 0.014). There was a significant difference (p = 0.011) in the rate of failures because of nonunion (eighteen patients with an iliac crest bone graft compared with six patients with the recombinant human bone morphogenetic protein-2 matrix). Also, the number of patients requiring second surgeries was significantly higher in the iliac crest bone-graft group (thirty-six patients) compared with the recombinant human bone morphogenetic protein-2 matrix group (twenty patients) (p = 0.015). The use of recombinant human bone morphogenetic protein-2 in instrumented posterolateral lumbar arthrodesis decreases operative time and blood loss and produces earlier and higher fusion rates than does iliac crest bone graft. Clinical outcomes are similar to those with iliac crest bone graft. Thus, the need for harvesting iliac crest bone is eliminated along with the morbidities associated with the harvest procedure.